The role of start-ups in structural transformation - Robert C. Dent; Fatih Karahan; Benjamin Pugsley; Ayşegül Şahin (Federal Reserve Bank of New York, 2016)
The U.S. economy has been going through a striking structural transformation - the secular reallocation of employment across sectors - over the past several decades. We propose a decomposition framework to assess the contributions of various margins of firm dynamics to this shift. Using firm-level data, we find that at least 50 percent of the adjustment has been taking place along the entry margin, owing to sectors receiving shares of start-up employment that differ from their overall employment shares. The rest is mostly the result of life cycle differences across sectors. Declining overall entry has a small but growing effect of dampening structural transformation.
Keywords: E24; J00; J23; L25; 330; structural transformation; employment dynamics; sectoral reallocation